2006
DOI: 10.1007/s10646-006-0104-2
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disruption in male mosquitofish (Gambusia holbrooki) inhabiting wetlands in Western Australia

Abstract: The use of gonopodial indices as potential indicators of endocrine disruption in the mosquitofish Gambusia holbrooki inhabiting south west Australian wetlands was investigated. A minimum of 50 mature males was collected from each of five water-bodies in the Swan Coastal Plain, Western Australia, in order to measure morphological features related to reproduction. A set of morphological measurements were used to derive the following indices: gonopodium length/standard body length, pre-anal length/standard body l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 12 publications
(25 reference statements)
1
17
0
4
Order By: Relevance
“…Drèze et al (2000) found that exposure of mosquito fish to 4-nonylphenol resulted in a significant reduction in both length and weight. Similar results have also been observed in several other polluted sites (Angus et al 2002;Game et al 2006). This trend was also noted in the presence of 17β-estradiol (up to 500 ng/L) exposure (Doyle and Lim 2002).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Drèze et al (2000) found that exposure of mosquito fish to 4-nonylphenol resulted in a significant reduction in both length and weight. Similar results have also been observed in several other polluted sites (Angus et al 2002;Game et al 2006). This trend was also noted in the presence of 17β-estradiol (up to 500 ng/L) exposure (Doyle and Lim 2002).…”
Section: Discussionsupporting
confidence: 88%
“…In natural systems that receive treated effluent, mosquito fish have been used as a common test scenario for environmental exposure to such contaminants (Batty and Lim 1999;Toft et al 2003;Leusch et al 2006). They have also been used as a tool in the initial assessment of contaminated lakes (Game et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…1995; Greytak et al, 2005;Game et al, 2006;Jessica et al, 2007). Our data suggest that H. malabaricus is a species with a high allostatic capacity (Wikelski and Cooke, 2006), using different mechanisms and adjustments of the set-point of steroid levels, which allow for survival and reproduction in polluted environments as a classical rheostatic response (Mrosovsky, 1990).…”
Section: Hormonal and Metabolic Adjustmentmentioning
confidence: 86%
“…Biomarkers of exposure (ethoxyresorufin- O -deethylase [EROD] activity and biliary metabolites) and biomarkers of effects (condition factor, liver somatic index, DNA damage and stress proteins) were measured at the end of the exposure period. These biomarkers have shown to be amongst the most relevant to identify impacts of xenobiotics on organisms [8][10]. The suite of biomarkers provides an indication of the potential impacts of exposure to drilling fluids on fish health, and assist environmental managers in the selection of environmentally acceptable drilling fluids.…”
Section: Introductionmentioning
confidence: 99%